Implementasi Total Quality Management (TQM) Dalam Pendidikan Islam: Strategi Mewujudkan Lembaga Pendidikan Yang Berkualitas Dan Berdaya Saing - Rosmiati Ramli; Nur Aisyah; Yenni Yenni; Muh Iqbal Muhidin (FKIP UNSULTRA, 2026)
Total Quality Management (TQM) is a management approach oriented toward continuous improvement to achieve customer satisfaction through the involvement of all organizational components. In Islamic education, the implementation of TQM is an important strategy for improving the quality of educational services, strengthening institutional management effectiveness, and enhancing competitiveness in the era of globalization and educational transformation. This article aims to analyze and synthesize the implementation of TQM in Islamic education and its strategic development for building high-quality and competitive educational institutions. This study uses a library research method by reviewing various scientific sources, including journals, books, proceedings, and relevant documents. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings show that the implementation of TQM in Islamic education is carried out through five main strategies: (1) orientation toward educational customer satisfaction, (2) quality-oriented leadership, (3) continuous improvement, (4) involvement of all school members in quality management, and (5) strengthening a quality culture based on Islamic values. These strategies not only enhance educational service quality but also strengthen teacher professionalism, learning effectiveness, and the development of students’ Islamic character. Therefore, TQM serves as an effective managerial approach to develop Islamic educational institutions that are excellent, adaptive, and sustainable in responding to modern educational challenges.